O uso do GeoGebra na resolução do problema da duplicação do cubo - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This paper presents an experience report referring to an unprecedented class for the author involving the study of cubic equations, carried out with a third-year class at Escola Estadual do Ensino Médio Yeté in the city of Tuparendi-RS. During this work, we sought to identify the contribution that technologies can provide, in the form of a stimulus for the development of logical reasoning and cognitive structures that contribute to the understanding of the contents addressed within the discipline of mathematics during the third year of high school. During this work, with the objective of understanding the possible contributions that the use of technologies could bring to the study of cubic equations, the GeoGebra software was used as a complementary tool in the teaching-learning process. The teacher's role in the course of the work boiled down to a posture of guiding agent, transferring to the student the role of protagonist in this constructive process of knowledge, enabling them, through experimentation, success and error, to formulate their own conclusions. Aiming to provide subsidies to create an environment for research and debate, a challenge was proposed involving the resolution of a problem with cubic cubic equations, where at first they were asked to try to find the solution and after testing them in GeoGebra. The evaluation of the work considered the evolution of mathematical thinking on the part of the students, when they managed, during the activity, to structure their ideas in line with the mathematical concepts previously worked on, which was enhanced with the use of the GeoGebra software, helping in a way forceful in the development of students' autonomy of thought.
Keywords: GeoGebra; Equações cúbicas; Construção; Autonomia; Protagonista; Cubic equations; Construction; Autonomy; Protagonist; CNPQ::CIENCIAS EXATAS E DA TERRA